Strategy on the Implementation of Good Agriculture Practice (GAP) in Smallholder Plantation to Improve the Production and Quality of Arabica Coffee Bean in Enrekang Regency Indonesia: Strategi Penerapan Good Agriculture Practices (GAP) pada Perkebunan Rakyat untuk Meningkatkan Produksi dan Kualitas Kopi Arabica di Kabupaten Enrekang, Indonesia - T, Irfansyah; Ridwan, Ifayanti; Ala, Ambo (Jurnal Agrivigor, 2021)
This study aims to determine the priority scale in the management of Arabica coffee plants based on Good Agriculture Practices (GAP) to increase the production, productivity and quality of Arabica coffee in smallholder coffee plantations. The research was conducted in three districts in Enrekang Regency, namely Baroko, Baraka, and Masalle District, respectively, from December 2017 to January 2018. The research was in the form of a survey (literature study, observation, and interviews), the sample selection was carried out using purposive sampling on 30 respondents from Agriculture and Plantation Office of Enrekang Regency, Extension officers, Famers Groups, and coffee plant experts. Quantitative descriptive data analysis using Expert Choice Version 11 was conducted on the survey results for determining the priority scale of GAP components for Arabica coffee. The study results show that the priority scale of applying GAP for coffee plants in Enrekang Regency was the cultivation aspect (46.7%) consisted of pruning, fertilization both types and application method of the fertilizer, pest and disease control, and varieties. Secon priority was the aspect of post-harvest (27.9%) followed by harvest aspect of 25.5%.